Implicit homophobic argument structure: equal marriage discourse in the Moral maze - Van der Bom, Isabelle; Coffey-Glover, Laura; Jones, Lucy; Mills, Sara; Paterson, Laura L. (John Benjamins Publishing, 2015)
This article analyses the linguistic and discursive elements which contribute to the production of implicit homophobia. Explicit homophobia has been well documented and strategies for countering discriminatory language have been developed (Baker, 2014; Leap, 2012). However, our interest here is in documenting implicit homophobia, where homophobic beliefs are only hinted at, are disassociated from the speaker, or are embedded within discursive and argument structures.